Nickel. - Wilder, Robert ([Place of publication not identified] : Leaf Storm Pr Llc, 2016)
A STORY OF LOVE, LOSS AND LOYALTY. Being a teenager is hard enough without your mother in rehab and your slightly inept stepfather doing his best not to screw things up. But at least, Coy has Monroe. Coy is a quirky teenage boy and his best friend Monroe is a girl who is just as odd and funny and obsessed with 80's culture as he is. So when Monroe comes down with a mysterious illness, his inner turmoil only grows. As Monroe gets sicker and Coy gets a girlfriend from another social crowd, the balance tips and Coy has to figure out how not to give up on his friend, his family, or himself. Nickel is a hilarious, heartbreaking and honest portrayal of the complicated world of being a teenager today.
Keywords: Nineteen eighties -- Fiction